As santas missões populares na Diocese de Mossoró 2005-2008: à luz do magistério da igreja. - Melo, Wescley Paulo Pereira de (2019)
The mission in the history of the Church has always been an important action to make Jesus Christ announced and known to the human being. We find in several biblical passages the missionary instruction to bring to the ends of the earth the Good News of Salvation. The missionary perspective gained prominence in the Church of the twentieth century inspired by the ecclesiology of the Second Vatican Ecumenical Council continued by other documents of the Magisterium. The ecclesiological and missiological character was so marked by its Constitutions and decrees. In intuiting the Church's evangelizing action in the local context, the theme of this research is about the mission in the Diocese of Mossoró 2005-2008: in the light of the Magisterium of the Church. We will try to understand what their priority actions were to animate communities of faith according to the discipleship and the missionary nature of Christ. And discern how to tread new paths for the continuity of the mission entrusted by Christ to his Church. Because it deals with the evangelizing dimension, it is perceived that the research encompasses the continued mission of the missionary disciple. New actions are designed so that the Church's action in the world can be updated according to the missionary dynamic. This was the path adopted in the Church throughout Latin America, especially in Brazil, and reflected in the western region of Potiguar. The problem revolves around an authentic, continuous and effective mission. How to understand, think and accomplish the mission? How to be more present in people's lives? Our goal is to look at an outgoing church, but it needs to actualize the essentials of mission as inherent in the life of the Church. It will be avoided in this way resumes itself to strong moments, running the risk of being denominated of events, and the essential of the mission becomes secondary. The dissertation typology to be applied in the present research will be done through primary documents, minutes of meetings and bibliographical researches. Endorsed by the theoretical reference: Lumen Gentium, Gaudium et Spes and Ad Gente; to later in the Evangelli Nuntiandi of Paul VI; in V CELAM; in Evangelli Gaudium de Francisco; and José Comblin. The development of the work presents the need for the local Church to live the ongoing, permanent mission.